Dose-dependent incidence of agranulocytosis in patients treated with methimazole and propylthiouracil - Jaeduk Yoshimura Noh; Kosuke Inoue; Nami Suzuki; Ai Yoshihara; Miho Fukushita; Masako Matsumoto; Hideyuki Imai; Shigenori Hiruma; Masahiro Ichikawa; Masakazu Koshibu; Akiko Sankoda; Rei Hirose; et al. (Endocrine Journal)
Agranulocytosis is a serious adverse effect of methimazole (MMI) and propylthiouracil (PTU), and although there have been reports suggesting a dose-dependent incidence in relation to both drugs, the evidence has not been conclusive. The objective of our study was to determine whether the incidences of agranulocytosis induced by MMI and PTU exhibit dose-dependency. The subjects were 27,784 patients with untreated Graves’ disease, 22,993 of whom were on an antithyroid drug treatment regimen for more than 90 days. Within this subset, 18,259 patients had been treated with MMI, and 4,734 had been treated with PTU. The incidence of agranulocytosis according to dose in the MMI group was 0.13% at 10 mg/day, 0.20% at 15 mg/day, 0.32% at 20 mg/day, and 0.47% at 30 mg/day, revealing a significant dose-dependent increase. In the PTU group, there were 0 cases of agranulocytosis at doses of 125 mg/day and below, 0.33% at 150 mg/day, 0.31% at 200 mg/day, and 0.81% at 300 mg/day, also revealing a significant dose-dependent increase. The incidence of agranulocytosis at MMI 15 mg and PTU 300 mg, i.e., at the same potency in terms of hormone synthesis inhibition, was 0.20% and 0.81%, respectively, and significantly higher in the PTU group. Our findings confirm a dose-dependent increase in the incidence of agranulocytosis with both drugs, but that at comparable thyroid hormone synthesis inhibitory doses PTU has a considerably higher propensity to induce agranulocytosis than MMI does.